2020
DOI: 10.1088/1475-7516/2020/03/055
|View full text |Cite
|
Sign up to set email alerts
|

Observational signatures of wormholes with thin accretion disks

Abstract: We numerically construct images of thin accretion disks in rotating wormhole backgrounds, for the Kerr-like and the Teo class of wormholes. Our construction is illustrated by two methods, a semi-analytic scheme where separated null geodesic equations obtained by analytically integrating the second order equations once are used, as well as by a numerical ray-tracing method utilizing a fourth order Runge-Kutta algorithm. Our result shows dramatic differences between accretion disk images in wormhole backgrounds,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 67 publications
1
60
0
Order By: Relevance
“…Our analysis demonstrated that the accretion disk will appear in a qualitatively similar way to a distant observer and only quantitative differences will be present in its size and radiation intensity. The problem was also revisited in [46], and the optical appearance of wormholes with a thin accretion disk was investigated in [47]. This work is a natural continuation of our previous studies examining the observable features of a thin disk around the strongly naked Janis-Newman-Winicour singularity.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our analysis demonstrated that the accretion disk will appear in a qualitatively similar way to a distant observer and only quantitative differences will be present in its size and radiation intensity. The problem was also revisited in [46], and the optical appearance of wormholes with a thin accretion disk was investigated in [47]. This work is a natural continuation of our previous studies examining the observable features of a thin disk around the strongly naked Janis-Newman-Winicour singularity.…”
Section: Introductionmentioning
confidence: 80%
“…However, we should note that this is not the only mechanism, which can lead to the appearance of ring images. They can be observed for other exotic compact objects such as boson stars and wormholes possessing a photon region [47,48], where they are formed by different physical reasons. The images are obtained applying the visualization techniques developed in [45], which build on earlier studies on the optical appearance of a thin accretion disk around the Schwarzschild black hole [49][50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…This is a question of the same order as the origin of point naked singularities, as well as other exotic structures such as bosonic stars, wormholes, etc. [4][5][6][7][8][9][10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26]. We note, however, that for some sets of configuration parameters, it could be difficult to distinguish SS from ordinary black holes relying upon the accretion disk structures.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the motivations for many theoretical works devoted to non-canonical and even exotic solutions of General Relativity and its modifications, which could have similar astrophysical consequences. The non-exhaustive list below includes papers on various aspects of compact objects with naked singularities [4][5][6][7][8][9][10][11][12][13][14], with wormholes [15][16][17][18][19], boson stars [20][21][22][23][24], and the other non-singular objects mimicking the black holes [25][26][27]. The question arises as to how the aforementioned exotic configurations were formed; probably, not all corresponding models can reflect real astrophysical situations.…”
Section: Introductionmentioning
confidence: 99%
“…1a). They are increasingly attracting attention of physicists for many different reasons [1][2][3][4][5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, so far, there is no realistic physical model of a wormhole formation.…”
Section: Introductionmentioning
confidence: 99%